Insights to correlations and discrepancies between impaired lung function and heart failure in Eisenmenger patients. (February 2020) - Gumbiene, Lina; Kapleriene, Lina; Jancauskaite, Dovile; Laukyte-Sleniene, Monika; Jureviciene, Elena; Rudiene, Virginija; Paleviciute, Egle; Mataciunas, Mindaugas; Sileikiene, Virginija
Impaired lung function and spirometric signs of airway obstruction without common risk factors for chronic obstructive pulmonary disease could be found in patients with Eisenmenger syndrome. This study aimed to analyse the association between lung function parameters and disease severity (including heart failure markers, associated congenital heart defect) as well as the possible reasons for airflow obstruction in Eisenmenger syndrome. The data of 25 patients with Eisenmenger syndrome were retrospectively evaluated. The patients were divided into groups according to airflow obstruction and a type of congenital heart defect. Airflow obstruction was found in nearly third (32%) of our cases and was associated with older age and worse survival. No relation was found between airway obstruction, B-type natriuretic peptide level, complexity of congenital heart defect and bronchial compression. Most of the patients (88%) had gas diffusion abnormalities. A weak negative correlation was noticed between gas diffusion (diffusing capacity of the lung for carbon monoxide) and B-type natriuretic peptide level (r = −0.437, p = 0.033). Increased residual volume was associated with higher mortality (p = 0.047 and p = 0.021, respectively). A link between B-type natriuretic peptide and lung diffusion, but not airway obstruction, was found. Further research and larger multicentre studies are needed to evaluate the importance of pulmonary function parameters and mechanisms of airflow obstruction in Eisenmenger syndrome.